Bilingualism in Gadis Pantai Novel by Pramoedya Ananta Toer - Achmad Suherman; Agus Sulaeman (Journal of English Education and Teaching, 2020)
The background of this study begins from people who rarely use monoligual language (one language). But in daily life, there are still many people who use two languages (bilingualism). People who use local languages and Indonesian language for example. The purpose of this study is to describe bilingualism in novels as a sociolinguistic study that examines language in assessment with the user community. This research is used to provide information to readers about the bilingualism in Gadis Pantai (The Girl from the Coast) by Pramoedya Ananta Toer. This study uses qualitative research with content analysis methods. The data source used in this study is primary data in the form of novel as the main data source. Secondary data of this study are reference books that support the study conducted by researchers. This research is useful for studying bilingualism in Gadis Pantai by Pramoedya Ananta. From the results of the study and discussion it can be concluded that Gadis Pantai by Pramoedya Ananta Toer contains 25 sentences in bilingualism. Bilingualism that is found is between Javanese language and Indonesian language but indonesian dominated. Bilingualism is not only found directly in the communication of the language community but also can be found in literary works. This type of literary work can be in the form of a novel. Bilingualism in novels is found in conversations between characters in the novel.